2006
DOI: 10.5458/jag.53.149
|View full text |Cite
|
Sign up to set email alerts
|

N-Linked Oligosaccharide Processing Enzymes as Molecular Targets for Drug Discovery

Abstract: α Glucosidases (EC 3.2.1.20) are also exo acting carbohydrases, catalyzing the release of α D glucopyranose from the non reducing ends of various substrates, 1,2) and on the basis of amino acid sequence similarities, α glucosidases are classified into two families, family 13 and family 31. 3,4) Endoplasmic reticulum (ER) glucosidases, glucosidase I (EC 3.2.1.106) and glucosidase II (EC 3.2.1.84), are key enzymes in the biosynthesis of asparagine linked oligosaccharides that catalyze the first processing event … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…We have examined the substrate specificity ofglycosidases for inhibitor design using synthetic small molecules [12][13][14][15][16][17][18][19][20][21], some of which are summarized in Fig. (1).…”
Section: Acquisition Of the Enzymological Information Ofglucosidases mentioning
confidence: 99%
“…We have examined the substrate specificity ofglycosidases for inhibitor design using synthetic small molecules [12][13][14][15][16][17][18][19][20][21], some of which are summarized in Fig. (1).…”
Section: Acquisition Of the Enzymological Information Ofglucosidases mentioning
confidence: 99%
“…9 The planar catechin also shows several biological activities, such as remarkable a-glucosidase inhibition, and anti-virus and anti-tumour activities. 7d, 10 We report herein that the enhanced radioprotective activity of the planar catechin against X-ray induced apoptosis in rat thymocytes compared to that of (+)-catechin. The biological data using rat thymocytes together with chemical data, such as radical-scavenging rates of the catechins as well as their lipophilicity provide fundamental and valuable information to develop effective radioprotective agents without toxicity.…”
Section: Introductionmentioning
confidence: 82%
“…As a-glycosidase catalyzes theˆnal step in the digestive process of carbohydrates, the strong inhibitory eŠect on a-glycosidase suggested that PCA may be used as a lead compound for the development of antidiabetic therapeutics, similar to acarbose and voglibose which are known to reduce postprandial hyperglycemia primarily by interfering with carbohydrate digesting enzymes and delaying glucose absorption. Potent antiviral activity of PCA was also shown by signiˆcant inhibition of Newcastle Disease Virus infection of BHK cells (24). Considering the strong inhibitory eŠect on a-glucosidase, the antiviral activity of PCA may be attributed to inhibition of glucosidase during protein synthesis that is essential for virus proliferation (25).…”
Section: Biological Propertiesmentioning
confidence: 99%